A Trickle-Down Theory of Incentives with Applications to Privatization and Outsourcing - Fredrik Andersson (Research Institute of Industrial Economics (IFN), 2009)
The make-or-buy decision is analyzed in a three-layer principal-management-agent model. There is a cost-saving/quality tradeoff in effort provision. The principal chooses between employing an in-house management and contracting with an independent management; the cost-saving incentives facing the management are, endogenously, weaker in the former case. Cost-saving incentives trickle down to the agent, affecting the cost-saving/quality trade-off. It is shown that weak cost-saving incentives to the management promote quality provision by the agent, and that a more severe quality-control problem between the principal and the management, as well as a higher valuation of quality, make an in-house management more attractive.
Keywords: D23; L22; L24; 330; Make-or-buy decision; Multitask principal-agent problem; Outsourcing; Make or Buy; Privatisierung; Outsourcing; Theorie